Structural brain abnormalities in early-onset schizophrenia - Ferrari,Maria Cristina Lombardo (2006)
BACKGROUND: Few studies investigated brain abnormalities in early onset schizophrenia. OBJECTIVE: To assess computed tomography (CT) abnormalities in patients with childhood or adolescence onset schizophrenia. Method: CT scans of patients with childhood (6 to 11 years old) (N=6) or adolescence (12-17 years old) (N=9) schizophrenia were compared to normal controls. Patients were diagnosed based on the DSM-III-R criteria. Ventricular enlargement was measured by the Ventricle to Brain Ratio (VBR) and Cortical Atrophy (pre-frontal prominence) was measured by the Pre-Frontal Atrophy Index (PFAI). RESULTS: There was a significant difference in VBR, but not in PFAI, between subjects and controls [8.26±2.79, and 5.71±3.26 (p=0.029)], and [2.72±1.77, and 3.21±1.53 (p=0.424)], respectively. There were no differences of VBR and PFAI between children and adolescents with schizophrenia. CONCLUSION: Compared to controls, patients with child or adolescent onset schizophrenia exhibit more pronounced ventricular enlargement. There were no differences regarding prefrontal atrophy.